Уточнение формулы тягового усилия электромагнитных контакторов и реле - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
A new formula for the tractive force of a contactor (relay) on the basis of a special expansion of jump-like input voltages is constructed.